Can you trust your car? [automotive electronics reliability testing]. - Berger, I. (IEEE spectrum)
Car electronics-especially those under the hood that control the throttle, the antilock brakes and other safety-critical systems-should work in kinds of weather. This paper describes how, to ensure reliability, carmakers test these electronics, and the cars, in special weather chambers